Study of Molecular and Ionic Vapor Composition over CeI3 by Knudsen Effusion Mass Spectrometry - Dunaev, A. M.; Motalov, V. B.; Kudin, L. S.; Butman, M. F.; Krämer, K. W. (Journal of Spectroscopy, 2016)
The molecular and ionic composition of vapor over cerium triiodide was studied by Knudsen effusion mass spectrometry. In the saturated vapor over CeI3 the monomer, dimer, and trimer molecules and the negative ions I−, CeI4-, and Ce2I7- were identified in the temperature range of 753–994 K. The partial pressures of CeI3, Ce2I6, and Ce3I9 were determined and the enthalpies of sublimation, ΔsH°(298.15 K) in kJ·mol−1, in the form of monomers (298±9), dimers (415±30), and trimers (423±50) were obtained by the second and third laws of thermodynamics. The enthalpy of formation, ΔfH°(298.15 K) in kJ·mol−1, of the CeI3 (-371±9), Ce2I6 (-924±30), and Ce3I9 (-1585±50) molecules and the CeI4- (-857±19) and Ce2I7- (-1451±50) ions were calculated. The electron work function, φe = 3.3±0.3 eV, for the CeI3 crystal was evaluated.